Linear integral equations of the third kind arising from neutron transport theory - Shulaia, D. (Mathematical methods in the applied sciences, 2007)
The aim of this paper is to study, in the class of Hölder functions, linear integral equations with coefficients cos x having zeros in an interval under consideration. Using the theory of singular integral equations, necessary and sufficient conditions for the solvability of these equations under some assumptions on their kernels are given. The kernels of transport equations satisfy the required assumptions. Copyright © 2007 John Wiley & Sons, Ltd.